ANALISIS KINERJA WAKTU DAN BIAYA PROYEK KONSTRUKSI DENGAN METODE EARNED VALUE ANALYSIS - Andi Marini Indriani; Gunaedy Utomo; Muhammad Rizqy (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2022)
The International Airport Sultan Aji Muhammad Sulaiman (SAMS), Sepinggan Balikpapan is the gateway to East Kalimantan and is an airport with high aircraft movements every year. Periodic maintenance must be carried out to support airport performance. Runway surface overlay and paved shoulders is one of the works carried out for this purpose. In a construction project, good management is needed to control so that the project runs according to the planned time and cost. Earned Value Analysis (EVA) is one method that can be used to control projects. After analyzing using project data from week 1 to week 47, it is known that the costs incurred are greater than the budgeted value, this is indicated by the CPI value = 0.998. The implementation time is faster than the planned schedule, as seen in the SPI value of 1.142. The result of the final calculation of the project which indicates a loss and an estimated turnaround time of 65 weeks indicates a 4 week acceleration.